Digital Comic Strips Integrated with 4C Skills of the 21st Century for Syntax Learning - Sainil Amral; Sumiharti Sumiharti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
The study aims to develop integrated comic strip learning media for 4C skills in the 21st-century education era for syntax classes. The research approach used a mixed method through the R and D (Research and Development) method and the Borg and Gall model. This research was conducted in the 2023-2024 academic year at the Indonesian Language and Literature Education Study Program, at Jambi University in the even semester. The participants in this study were 2 lecturers teaching the Syntax course, 2 experts (teaching and learning material and curriculum), and 100 students. The data collection consisted of observation, documents, tests, and questionnaires. Data analysis techniques refer to qualitative and quantitative data analysis. In conclusion, the integrated comic strip learning media with 4C skills for syntax classes was considered feasible and effective in improving student learning performance. Digital comic strips had an impact on syntax learning outcomes and built quite significant reading habits. The results of this study have implications for developing a learning media framework involving digital technology.